The Neural Pathways and Evolutionary Supports for the Nociceptive-Sympathetic Coupling of Pain Sensation Hypothesized by the Athletes of NBA in Television - Zi-Jian Cai (Advancement and New Understanding in Medical Science Vol. 8, 2024)
It was proposed by the US athletes of National Basketball Association (NBA) in television on May 6, 2016, that the pain sensation might result from the nociceptive-sympathetic coupling after the peripheral nociceptive afferents. In this article, it is supplemented the neural pathways and evolutionary supports for this nociceptive-sympathetic coupling. For the neural circuits of pain sensation, presently it is widely accepted that the A\(δ\)- and C-fibers relay the nociceptive signals to the laminae I, II and V at dorsal spinal horn, and in turn activate the periaqueductal grey (PAG) in midbrain sending inhibitory feedbacks via raphe to the spinal nociceptive transmission. Herein it is supplemented that, besides such feedback pain circuits, the neurons in laminae I and V of dorsal spinal horn and those in PAG can directly activate the sympathetic outputs, completing the nociceptive-sympathetic coupling. It is suggested that such nociceptive-sympathetic coupling partially contribute to the pain sensation because of the sympathetically maintained pain. Furthermore, by the evidence of somite nociceptive coupling in Drosophila, it is additionally supported by evolution the nociceptive-sympathetic coupling for pain sensation at spinal cord in vertebrates. In all, it is delineated the neural pathways and supplemented the evolutionary supports for the nociceptive-sympathetic coupling of pain sensation.